Penafsiran Struktur Geologi di Daerah Gunung Batu Lembang Berdasarkan Korelasi Data Permukaan dan Geofisika - G.M. Lucki Junursyah; Geni Agustya (Pusat Survei Geologi, 2017)
Gunung Batu is composed by andesite dike intrusion rock, leaning towards the north formed a scarp, as part of the Lembang Fault that extends towards the west-east. The subsurface geological structure conditions and its relations to sedimentation in the western part is not clearly understood yet. For more detail investigation, it is necessary to conduct geophysical measurements of 2D Resistivity to interpret the lithostratigraphy vertically and geomagnetic to determine the lateral distribution of lithological boundary. Furthermore, geological investigation is applied by measuring the joints of Gunung Batu's scarp. The subsurface geological structure conditions and its relations to sedimentation in the western part is not clearly understood yet. For more detail investigation, it is necessary to conduct geophysical measurements of 2D Resistivity to interpret the lithostratigraphy vertically and geomagnetic to determine the lateral distribution of lithological boundary. Furthermore, geological investigation is applied by measuring the joints of Gunung Batu's scarp. The second order fault formed as dextral-normal oblique fault lineament relative to the 310°-0° (northwest-southeast) and sinistral-normal oblique fault lineament relative to the 0°-40° (northeast-southwest). This fault is assumed dominantly influenced by the extensional force.Keywords: Gunung Batu, Lembang Fault, 2D resistivity method, Geomagnetic method.